Synergistic effects of high-temperature curing and elemental conditioning on red mud-based geopolymer: Compressive strength and immobilization - Dongliang Luo; Yufeng Du; Jintao Zhang; Feiyong Chen; Yang Song (PLoS ONE, 2026)
Red mud, a by-product of alumina refining, is accumulating rapidly and harming ecosystems. This study converted red mud and fly ash into a geopolymer (RFGP) to create value while mitigating waste. The effects of different sodium silicate moduli and red mud contents on the compressive strength and microstructure (as characterized by SEM, XRD, TG, and FTIR) of RFGP cured for 28 days were systematically analyzed. The results showed that the compressive strength of RFGP decreased with the increase of sodium silicate modulus and red mud content, with minimum 28-day values of 9.65 MPa and 12.81 MPa, respectively. It was found that the percentages of SiO 2 , Al 2 O 3 , and CaO in the raw materials were directly proportional to the compressive strength, while Na 2 O and Fe 2 O 3 were inversely proportional thereto. Therefore, the chemical composition of substances in the raw material had an important influence on the compressive strength. In addition, the environmental safety of RFGP was evaluated. After the polymer reaction, the heavy metal ions in RFGP were transformed into more stable forms, with the concentration of Hg being significantly reduced, meeting the requirements of applicable environmental standards. This synergistic utilization of industrial by-products demonstrated a viable pathway for the sustainable valorization of hazardous wastes as value-added construction materials.